AKIBAT HUKUM TERHADAP PPAT ATAS TIDAK MEMBAYARKAN UANG BPHTB YANG TELAH DITITIPKAN KEPADANYA BERKAITAN DENGAN PERALIHAN HAK MELALUI AKTA JUAL BELI (STUDI PUTUSAN NOMOR 300/Pid.B/2015/PN.Dps) - INDARSI UNTHARI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. Dr. Budiman Ginting, SH, MHum2. Dr. T. Keizerina Devi A, SH, CN, MHum3. Notaris Dr. Suprayitno, SH, MKn Paying BPHTB (Land and Building Right Transfer Tax) is principally anobligation of a taxpayer and is not the obligation of PPAT (Land Title Registrar).PPAT can only help the client to deposit the money to pay the tax. PPAT only triesto provide best service for his client by receiving the client’s money to beentrusted to pay BPHTB. This is a normative legal research, which usessecondary data to answer the problems discussed. The data are obtained fromlibrary research. The theory of liability and justice are employed in this research.The results of the research conclude that the PPAT is obliged to deposit themoney entrusted to him for the payment of BPHTB regarding the right transfer ina sale and purchase deed although it is not stipulated in the prevailing laws andregulations. The PPAT who does not deposit the money entrusted to him will havelegal consequences. He is responsible for the obligation of paying BPHTB, but hedoes not deposit the money to the State or Regional Treasury Fund. Thus, itcauses financial loss to the other party as stated in Article 1365 of the Civil Codeand it is also categorized into an illegal action in penal law i.e. embezzlementpursuant to Article 372 of the Penal Code. The results of the analysis of theRuling No. 300/Pid.B/2015?PN.DpsKeywords: PPAT, BPHTB, Right Transfer, Sale and Purchase Deed